Bicycle aerodynamics: an experimental evaluation methodology - Chowdhury, H.; Alam, F. (Sports Engineering, 2012)
Aerodynamically efficient sports equipment/accessories and athlete body postures are considered to be the fundamental aspect to achieve superior performance. Like other speed sports, the aerodynamic optimisation is more crucial in cycling. A standard full-scale testing methodology for the aerodynamic optimisation of a cyclist along with all accessories (e.g., bicycle, helmet, cycling suit, shoes and goggle) is not well developed, documented, and standardised. This paper describes a design and development of a full-scale testing methodology for the measurement of aerodynamic properties as a function of cyclist body positions along with various accessories over a range of wind speeds. The experimental findings indicate that the methodology can be used for aerodynamic optimisation of all cycling sports.